2008
DOI: 10.1111/j.2044-8260.2008.tb00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Subscales measuring symptoms of non‐specific depression, anhedonia, and anxiety in the Edinburgh Postnatal Depression Scale

Abstract: It was concluded that there is now sufficient evidence that clinicians should not assume the EPDS to be unidimensional, but should assess all three subscales when screening for susceptibility to post-partum depression and/or post-partum anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
146
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(176 citation statements)
references
References 65 publications
(110 reference statements)
25
146
1
4
Order By: Relevance
“…Criteria for model selection include previous evaluation with the English language version of the EPDS or advancement in the literature as a good-fitting model in a postpartum sample. The models evaluated included the: (1) original unidimensional model of Cox et al (1987), (2) twofactor (depression, anxiety) model of Phillips et al (2009), (3) the three-factor (anhedonia, anxiety, and depression) model of Tuohy and McVey (2008), (4) a two-factor (depression, anxiety) version of the Brouwers et al (2001) model, and (5) a two-factor version of the Ross et al (2003) model. Two models (Brouwers et al 2001;Ross et al 2003) were originally three-factor models, both with only item 10 loading on a third factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Criteria for model selection include previous evaluation with the English language version of the EPDS or advancement in the literature as a good-fitting model in a postpartum sample. The models evaluated included the: (1) original unidimensional model of Cox et al (1987), (2) twofactor (depression, anxiety) model of Phillips et al (2009), (3) the three-factor (anhedonia, anxiety, and depression) model of Tuohy and McVey (2008), (4) a two-factor (depression, anxiety) version of the Brouwers et al (2001) model, and (5) a two-factor version of the Ross et al (2003) model. Two models (Brouwers et al 2001;Ross et al 2003) were originally three-factor models, both with only item 10 loading on a third factor.…”
Section: Discussionmentioning
confidence: 99%
“…Of published principal components analysis (PCA) and exploratory factor analysis (EFA) reported in English in both postpartum and prenatal samples, only Berle et al (2003) confirmed a unidimensional structure of the EPDS using a Norwegian sample. The vast majority of the literature suggests that the EPDS may represent factors in addition to depression, including anxiety (Adouard et al 2005;Astbury et al 1994;Matthey 2008;Phillips et al 2009;Pop et al 1992), anxiety and anhedonia (Chabrol and Teissedre 2004;Montazeri et al 2007;Tuohy and McVey 2008), or anxiety and suicide (Brouwers et al 2001;Jomeen and Martin 2005;Ross et al 2003;Tuohy and McVey 2008). Guedeney and Fermanian (1998) also identified two factors but conceptualized them as depressive symptoms (which included items commonly associated with the anxiety factor in other studies) and depressive mood.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Dysregulated affect in reproductive mood disorders includes increased negative affect (i.e., irritability, anger, sadness, and anxiety), decreased positive affect (i.e., anhedonia), and affective lability (233,329), while functional impairment is defined by clinically significant distress or disability in social, occupational, or other important activities (6). Reproductive mood disorders include PMDD, PPD, and perimenopausal depression.…”
Section: The Role Of Gonadal Steroids In Reproductive Mood Disordersmentioning
confidence: 99%